Responses of African Pentecostal churches to African refugees in Düsseldorf between 2015 and 2020 : a case study of mission and migration - Gyasi, Charles (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.